THE POLITICAL SYSTEM AS A FACTOR OF ENSURING THE INSTITUTIONAL CAPACITY OF THE STATE: A COMPARISON OF THE USA AND UKRAINE - HAPONENKO, Vira (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study examines the institutional development of Ukraine’s political system as a key factor in ensuring the state’s institutional capacity. A comparison with the political system of the USA reveals the main differences and similarities in approaches to institutional development and their impact on public administration. Historical prerequisites, legal foundations, and contemporary challenges faced by the state as a subject of social relations are analyzed. Special attention is given to the role of institutions in ensuring the stability, efficiency, and transparency of public administration. The interaction between different branches of government, the influence of civil society, and international organizations on the institutional development of the political system as a factor in ensuring the state’s institutional capacity are analyzed and highlighted. A comprehensive analysis of the institutional development of the political system and the economic component of public administration in the USA and Ukraine is conducted, identifying the main problems and providing recommendations for enhancing the state’s institutional capacity in Ukraine. The analysis of the historical prerequisites for the development of the political systems of the USA and Ukraine allows us to understand how past events and decisions have influenced the current state of institutional capacity. In particular, it is shown that in the USA, a long history of democratic development and stable institutions has contributed to the formation of an effective system of public administration. In Ukraine, however, frequent changes in political course and instability have posed certain challenges to the institutional development of the political system. It is found that the legal foundations on which the political systems of both countries are based also significantly impact their institutional capacity. In the USA, a constitutional system with a clear separation of powers and checks and balances ensures the stability and efficiency of public administration. In Ukraine, the legal system requires further reforms to ensure greater transparency and accountability. The contemporary challenges faced by both countries include issues of security, economic stability, and social justice. In the USA, a developed system of institutions allows for effective responses to these challenges, while in Ukraine, it is necessary to strengthen institutional capacity to adequately address modern threats. The interaction between different branches of government is emphasized as an important aspect of institutional development. In the USA, clearly defined powers and responsibilities of each branch of government contribute to the effective functioning of the political system. In Ukraine, frequent conflicts between branches of government necessitate the improvement of mechanisms for interaction and cooperation. The influence of civil society and international organizations on institutional development is also an important factor. In the USA, an active civil society and cooperation with international organizations contribute to strengthening institutional capacity. In Ukraine, it is necessary to enhance the role of civil society and effectively utilize international assistance for institutional development. The results of the study can be useful for developing recommendations to improve Ukraine’s institutional capacity based on the experience of the USA. The identified problems and proposed recommendations can serve as a basis for further reforms and the improvement of Ukraine’s political system.